FDA's Strategies to Close the Health Equity Gap among Diverse Populations - Jovonni Spinner; RADM Richardae Araojo (SAGE Publishing, 2021)
This commentary provides an overview of the Food and Drug Administration's Office of Minority Health and Health Equity.